Characterizing Foxp3+ and Foxp3- T cells in the homeostatic state and after allo-activation: resting CD4+Foxp3+ Tregs have molecular characteristics of activated T cells - Liu, Zilei; Baines, Katherine J.; Niessen, Natalie M.; Heer, Munish K.; Clark, David; Bishop, G. Alexander; Trevillian, Paul R. (Frontiers in Immunology, 2024)
Due to the intracellular expression of Foxp3 it is impossible to purify viable Foxp3 + cells on the basis of Foxp3 staining. Consequently CD4 + Foxp3 + regulatory T cells (Tregs) in mice have mostly been characterized using CD4 + CD25 + T cells or GFP-Foxp3 reporter T cells. However, these two populations cannot faithfully represent Tregs as the expression of CD25 and Foxp3 does not completely overlap and GFP + Foxp3 + reporter T cells have been reported to be functionally altered. The aim of this study was to characterize normal Tregs without separating Foxp3 + and Foxp3 -cells for the expression of the main functional molecules and proliferation behaviours by flow cytometry and to examine their gene expression characteristics through differential gene expression. Our data showed that the expressions of Foxp3, CD25, CTLA-4 (both intracellular and cell surface) and PD-1 was mostly confined to CD4 + T cells and the expression of Foxp3 did not completely overlap with the expression of CD25, CTLA-4 or PD-1. Despite higher levels of expression of the T cell inhibitory molecules CTLA-4 and PD-1, Tregs maintained higher levels of Ki-67 expression in the homeostatic state and had greater proliferation in vivo after allo-activation than Tconv. Differential gene expression analysis revealed that resting Tregs exhibited immune activation markers characteristic of activated Tconv. This is consistent with the flow data that the T cell activation markers CD25, CTLA-4, PD-1, and Ki-67 were much more strongly expressed by Tregs than Tconv in the homeostatic state.